Prevalence rate of osteoporosis complications in Ulan-Ude residents - T. I. Batudaeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
We studied the frequency of osteoporotic fractures of different localizations in patients of 40 years and older living in Ulan-Ude. It was revealed that women have osteoporotic fractures 2,4 times more often than men. Elder patients suffer low-energy fractures more often than younger ones. Buryat residents of Ulan-Ude had osteoporotic fractures twice more often than Russian ones. The frequency of fractures of all studied localizations among men and women of different race did not differ. Women more often had fractures of the distal forearm, men more often had broken ribs.